1999
DOI: 10.1029/1998rg900003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular environmental geochemistry

Abstract: Abstract. The chemistry, mobility, and bioavailability of contaminant species in the natural environment are controlled by reactions that occur in and among solid, aqueous, and gas phases. These reactions are varied and complex, involving changes in chemical form and mass transfer among inorganic, organic, and biochemical species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 171 publications
0
35
0
Order By: Relevance
“…The efficiency and reversibility of arsenite adsorption on iron sulfide, iron oxide, iron hydroxide, and phyllosilicate minerals in natural systems depend on many factors, including pH, dissolved arsenic concentration, type of mineral substrate, and presence of competing species, and are thus difficult to predict quantitatively. In general, however, precipitation is a more complete and stable mechanism for removal of solutes from solution than adsorption (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency and reversibility of arsenite adsorption on iron sulfide, iron oxide, iron hydroxide, and phyllosilicate minerals in natural systems depend on many factors, including pH, dissolved arsenic concentration, type of mineral substrate, and presence of competing species, and are thus difficult to predict quantitatively. In general, however, precipitation is a more complete and stable mechanism for removal of solutes from solution than adsorption (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of chromium, these changes can affect the macroscopic properties of toxicity and mobility in the atmosphere and in the geologic subsurface [1][2][3]. These behavioral attributes have motivated research into surface speciation of Cr-bearing surfaces, with the intent of correlating the explicit chemical form of the metal with transport and toxicity.…”
mentioning
confidence: 99%
“…A systematic study of the reactions with H 2 O showed that ions containing undercoordinated metal centers would undergo either addition or radical abstraction reactions [29]. These reactions would proceed in series until a Cr coordination number of 4 was reached, except for CrO 3 Ϫ , which was unreactive. The reactions of the chromium oxyanions with O 2 were also significant, and the present study describes these in detail.…”
mentioning
confidence: 99%
“…[3] The environmental implications of mineral surface chemistry are manifold and diverse. They include atmospheric CO 2 drawdown associated with silicate mineral dissolution, [4,5] removal from solution of adsorptive metal and oxyanion contaminants, [6] nutrient retention for plant growth [7] and organic matter stabilisation against microbial biodegradation. [8] Through a combination of macroscopic experiments, molecular spectroscopy studies, and molecular modelling, environmental chemists are developing an improved understanding of the molecular-scale controls over the rates and extents of mineral surface reactions.…”
mentioning
confidence: 99%